1994
DOI: 10.1002/mpo.2950220205
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate content in squamous cell carcinoma of the head and neck after low‐dose methotrexate

Abstract: Eleven patients with squamous carcinoma of the head and neck who were scheduled for surgical resection or endoscopic biopsy of tumor received 15 mg/m2 of methotrexate (MTX). Samples of tumor, normal mucosa, and plasma were obtained at surgery or endoscopy, 18-24 hours after the last MTX dose. Tissue content and plasma concentration of MTX and folate were measured using sequential radioligand-binding assays. Median MTX content was 50.0 pmol/g wet weight in tumor, 19.0 in normal mucosa, and < 0.5 nM (pmol/ml) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…[11] The biological reason for this apparent difference may be related to the finding that the dihydrofolate reducatase content in human squamous-cell carcinomas is low and easily saturable by even low doses of Methotrexate. [12,13] The present study has several weaknesses inherent in its retrospective design. Systematic evaluation of quality of life or pain scores was not done.…”
Section: Discussionmentioning
confidence: 92%
“…[11] The biological reason for this apparent difference may be related to the finding that the dihydrofolate reducatase content in human squamous-cell carcinomas is low and easily saturable by even low doses of Methotrexate. [12,13] The present study has several weaknesses inherent in its retrospective design. Systematic evaluation of quality of life or pain scores was not done.…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported to saturate the tumor cell dihydrofolate reductase at this dose, and further augmentation of the dose will be devoid of any benefit. 14 In the present study, metronomic therapy was used as an alternative to the standard conventional treatment approach considering the challenges of a resourceconstrained country. This constraint-adapted approach has helped us to tide over the challenges faced.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested an increased capillary endothelial permeability in tumour vessels compared with vessels in healthy tissue [16][17][18][19]. Therefore we obtained, at approximately the same time, a sample of healthy connective tissue supplied by the same tumour-serving artery to compare the uptake of labelled methotrexate in tumour and in healthy tissue.…”
Section: Discussionmentioning
confidence: 99%